“Loving nursing” and “taking responsibility” - Clinton, Michael (2018)
Transitioning to practice is challenging for baccalaureate nursing students. In baccalaureate nursing programs, the process typically begins in the junior year. A Successful transition depends on how well students apply their developing knowledge during clinical placements. A cross-sectional, multisite, qualitative study was conducted at four universities in Greater Beirut, Lebanon. In total, 35 junior baccalaureate students participated in audio-recorded focus group discussions. Thematic analysis was used to analyze the data. Three themes were sufficient to summarize the students experiences: “being unprepared,” “learning unexpected lessons,” and “taking responsibility.” Three subthemes, revising expectations, discovering divergence, and self-monitoring, were used to clarify the unexpected lessons students learned during clinical placements and how students responded. “Loving nursing and protecting yourself,” making the most of every day, and doubting future readiness were subthemes within the “taking responsibility” theme. Students troubled by nursing practices that diverged from their expectations monitored themselves to avoid falling into poor practices and kept track of the nursing procedures they performed. Only by taking responsibility for their learning, could students develop the competencies they will need as registered nurses. Faculty, clinical instructors, hospital administrators, nurse managers, and registered nurses need to do more to support students to take control of their learning.